Impact Of Technology And Information After A Period Of Pademi For Education And Health In Indonesia - Aulia Hervi Anggraini; Haura Karlina; Ratna Utami Wijayanti; Wahyu Wismanto Hadi (CV. Inara, 2022)
Technology has also influenced various sectors, an example of technological development is the emergence of application software that makes it easier for companies.But not only that, one type of form of technology that is growing rapidly in the era of pademi is information and Communication Technology in the field of Education. With the existence of social media, the younger generation takes advantage of this to take part and influence the community by showing their intelligence to set an example to the community through social media. One of the things that need to be considered in creating a competitive advantage for culinary, fashion, music, tourism industry players in the pademi era is Database Building and Management, namely the application of a platform that includes WhatsApp Business and email lists as a data container for potential repeat purchases by consumers. Since the pandemic conditions, consumers prefer to buy food, clothing, household items dal other delivery rather than come on the spot. Adaptation for behavior towards the new normal by developing strategies such as social distancing, health consider, cashless, less contact must also be implemented by existing businesses. In the context of business, technology can provide changes so as to create a new point of view in business known as digital marketing or internet marketing that utilizes the internet as a market medium. Conventional businesses are more concerned with purchases made by consumers. However, with a circular business model, how consumers can obtain goods and services is more important. Conventional business success focuses more on the material benefits gained from the sale of goods or services. They are result oriented. However, circular businesses are more concerned with how they can create a balance between environmental, social, and profit aspects.